Escherichia coli O121:H19 infection identified on microagglutination assay and PCR. Issue 5 (10th September 2015) - Sakai, Tomoyuki; Sawai, Toshihiro; Shimizu, Yasuyo; Morimune, Takao; Okuda, Yusuke; Maruo, Yoshihiro; Iyoda, Sunao; Takeuchi, Yoshihiro
Abstract: Non‐O157 Shiga toxin‐producing Escherichia coli (STEC) strains are increasingly recognized as foodborne pathogens that trigger hemolytic uremic syndrome (HUS). The detection and isolation of these strains is important, but distinguishing their bacteriological profiles is difficult. A 2‐year‐old girl developed HUS with mild renal involvement 22 days after consuming barbecued meat. Clinical and laboratory findings gradually improved without specific treatment. Because neither enterohemorrhagic E . coli (EHEC) nor Shiga toxins were detected in stool cultures in a clinical laboratory and the patient tested negative for circulating antibodies to O157 lipopolysaccharide, the case was initially diagnosed as probable atypical HUS. Subsequent serodiagnostic microagglutination assay and polymerase chain reaction‐based molecular testing, however, indicated the presence of the EHEC O121:H19 strain with stx2 . Thus, to correctly diagnose and treat HUS, a system for detecting non‐O157 STEC in a clinical setting is urgently needed.